Induction of mucosal immunity by pulmonary administration of a cell-targeting nanoparticle. (1st January 2021) - Kurosaki, Tomoaki; Katafuchi, Yuki; Hashizume, Junya; Harasawa, Hitomi; Nakagawa, Hiroo; Nakashima, Mikiro; Nakamura, Tadahiro; Yamashita, Chikamasa; Sasaki, Hitoshi; Kodama, Yukinobu
Abstract: We previously found that a nanoparticle constructed with an antigen, benzalkonium chloride (BK) and γ-polyglutamic acid (γ-PGA) showed high Th1 and Th2-type immune induction after subcutaneous administration. For prophylaxis of respiratory infections, however, mucosal immunity should be induced. In this study, we investigated the effect of pulmonary administration of a nanoparticle comprising ovalbumin (OVA) as a model antigen, BK, and γ-PGA on induction of mucosal immunity in the lungs and serum. The complex was strongly taken up by RAW264.7 and DC2.4cells. After pulmonary administration, lung retention was longer for the OVA/BK/γ-PGA complex than for OVA alone. OVA-specific serum immunoglobulin (Ig)G was highly induced by the complex. High IgG and IgA levels were also induced in the bronchoalveolar lavage fluid, and in vivo toxicities were not observed. In conclusion, we effectively and safely induced mucosal immunity by pulmonary administration of an OVA/BK/γ-PGA complex.